ANALYSIS OF THE IMPLEMENTATION OF THE IJARAH ASSET TO BE LEASED AGREEMENT IN THE LATEST DEVELOPMENT OF RETAIL SUKUK SALES IN INDONESIAN SHARIA BANK (CASE STUDY OF INDONESIAN SHARIA BANK KC S.PARMAN MEDAN) - Ramadhani, Anggraini; Anggraini, Tuti; Inayah, Nurul (JURNAL EKBIS, 2024)
The Indonesian government offers retail sukuk as an investment product for retail investors, in accordance with sharia principles. This research uses a qualitative research approach with a focus on case study methodology. The data sources used in this research consist of primary data obtained through observation and interviews. Meanwhile, secondary data was obtained from retail sukuk research and other relevant literature. The data validity method used in this research is called data source triangulation. The data analysis process begins with data collection, continues with organizing and categorizing the data, and finally identifying themes for interpretation. Therefore, the findings of this research include the results of the analysis of the implementation of SR 019-T3 retail sukuk at BSI KC S.parman Medan. The results of research findings and analysis will be presented as an illustration of how sales are carried out by banks, including a description of the obstacles and benefits faced. There are several advantages to investing in retail sukuk. However, retail sukuk also have their own risks. BSI is actively marketing retail sukuk through social media, and many students are starting to research retail sukuk and savings provided by SBSN agents or distribution partners.